Development strategy and commercial negotiations. Interview with Oswaldo Rosales, director of the International Trade and Integration Division of ECLAC - Romero, Marco (2007)
Estrategia de desarrollo y negociaciones comerciales, entrevista con Oswaldo Rosales, director de la División de Comercio Internacional e Integración de CEPAL.